محددات الاغتراب وتجلياته في أدب الدكتور زكي مبارك - معامير, محمد فيصل (University of Eloued جامعة الوادي, 2024)
تنهض هذه الدراسة على الوقوف عند محددات الاغتراب من حيث النشأة، وكيف اتخذ لنفسه مسارات تعريفية عقيب ذلك، ثم لنتخذ من حياة الدكتور زكي مبارك أنموذجا من خلال أدبه وما خلفه من آثار شعرية ونثرية، وبيان أهم الدواعي الذاتية والبواعث الموضوعية التي كمنت وراء تلك المحنة القاسية، وأخيرا الكشف عن أهم تجليات ظاهرة الاغتراب ومحاولة تفسيرها. Abstract: This study rises to stand at the determinants of alienation in terms of upbringing, and how it took for itself defining paths following that, then let us take from the life of Dr. Zaki Mubarak as a model through his literature and the poetic and prose effects he left behind, and to clarify the most important subjective reasons and objective motives that lay behind that yearning. Finally, the most important manifestations of the alienation phenomenon are revealed and an attempt is made to explain them.
محددات، الاغتراب، الدواعي الذاتية، البواعث الموضوعية، تجليات ظاهرة الاغتراب،الآثار الشعرية والنثرية. Key words: Determinants, alienation, subjective reasons, objective motives, manifestations of the phenomenon of alienation, poetic and prose effects.
Keywords: محددات، الاغتراب، الدواعي الذاتية، البواعث الموضوعية، تجليات ظاهرة الاغتراب،الآثار الشعرية والنثرية. Key words: Determinants; alienation; subjective reasons; objective motives; manifestations of the phenomenon of alienation; poetic and prose effects.